Spatiotemporal variation and driving force of gully erosion in the Pisha sandstone area - Zhang, Yu; Li, Long; Liu, Linfu; Zhang, Shangxuan; Zhao, Wenzhuo; Ren, Yanan; Yang, Yue (Frontiers in Environmental Science, 2024)
Debris slide, a typical method of gravity erosion, is the main source of coarse sand in channels in the pisha sandstone area.To precisely characterize the microtopography of slopes where debris slide occurs， employed the RIEGL VZ-400 3D laser scanner to scan the observation site,acquiring point cloud data of the slope microtopography. With the support of the "data conversion module" of Arc GIS software, the point cloud data is transformed into raster data, "3D analysis", "hydrological analysis" and "grid calculator" modules, the basic microgeomorphological indicators are extracted based on the gully slope grid data, and the erosion rate and microterrain evolution mechanism of gully slope in different seasons are determined. A gully slope with a slope of 80°-90°was selected as the research object to explore the relationship among gully slope erosion rates, microtopographical temporal and spatial variation trends, and driving factors in different seasons. Results revealed show the following: (1) In the pisha sandstone area, erosion was is relatively strong in the first quarter, with 65% of the area being eroded. The average erosion rates in the four quarters followed the order of first quarter > fourth quarter > second quarter > third quarter from fast to slow. (2) As the soil on the gully slope thawed, melt water increased soil moisture. This phenomenon sharply increased surface roughness in the first quarter. The correlation coefficients between erosion rate and temperature in the first and fourth quarters were 0.75 and 0.82, respectively. Temperature mainly affected erosion rate through surface roughness. The direct path coefficient of this effect was 0.72. (3) In the first and fourth quarters, temperature and wind speed are the main factors determining the erosion rate; the relationship between the surface roughness and other factors is obvious, so the surface roughness can be used as the best topographic factor for slope erosion in Pisha sandstone area.The results of the study aim to provide theoretical references for the study of the gravity erosion mechanism of gully slopes in the Pisha sandstone areas and to contribute to the quality development of the Yellow River Basin.